Challenging boundaries: is cross-protection evaluation necessary for African swine fever vaccine development? A case of oral vaccination in wild boar - Cadenas-Fernández, Estefanía; Barroso-Arévalo, Sandra; Kosowska, Aleksandra; Díaz-Frutos, Marta; Gallardo, Carmina; Rodríguez-Bertos, Antonio; Bosch, Jaime; Sánchez-Vizcaíno, Jose M.; Barasona, Jose A. (Frontiers in Immunology, 2024)
African swine fever (ASF) poses a severe threat to both domestic pig and wild boar (Sus scrofa) populations. The current epidemiological situation of the disease is more alarming than ever, impacting countries across five continents and causing devastating losses in the swine industry. Intensified efforts and extensive research have been undertaken to develop an effective and safe vaccine, but achieving this goal has proven exceptionally challenging. Live attenuated viruses (LAVs) have emerged as the most promising option for providing the highest level of protection against experimental challenges. However, the genetic and phenotypic variability of the virus leads to a vast diversity of ASF virus (ASFV) isolates, each with differences in virulence and distinct serotypes. Thus, LAVs may exhibit a limited ability to cross-protect against different ASFV isolates. This study sheds light on the limitations of a natural LAV (Lv17/WB/Rie1), known for its efficacy against a partially heterologous and highly virulent isolate (Arm07; II genotype), revealing its incomplete effectiveness against a much more phylogenetically distant virus (Ken06.Bus; IX genotype). These findings cast doubt on the feasibility of a universal vaccine against ASFV in the short term, underscoring the crucial need to establish the effectiveness limits of vaccine candidates against ASFV.